The hagiographical experiment developing discourses of sainthood - Gray, Christa 1982-; Corke-Webster, James (Brill, 2020)
"The Hagiographical Experiment: Developing Discourses of Sainthood throws fresh light on narratives about Christian holy men and women from Late Antiquity to Byzantium. Rather than focusing on the relationship between story and reality, it asks what literary choices authors made in depicting their heroes and heroines: how they positioned the narrator, how they responded to existing texts, how they utilised or transcended genre conventions for their own purposes, and how they sought to relate to their audiences. The literary focus of the chapters assembled here showcases the diversity of hagiographical texts written in Greek, Latin, Coptic, and Syriac, as well as pointing out the ongoing conversations that connect them. By asking these questions of this diverse group of texts, it illuminates the literary development of hagiography in the late antique, Byzantine, and medieval periods"--
Keywords: Geschichte; Hagiografie; Christliche Literatur; Christian hagiography / History and criticism; Christian literature / History and criticism; Konferenzschrift -- 2015 -- Edinburgh